P126 The Urgency Numeric Rating Scale (NRS): a novel patient-reported outcome measure to assess bowel urgency in adult patients with ulcerative colitis. (15th January 2020) - Dubinsky, M C; Naegeli DrPH, MPH, A; Dong, Y; Lissoos, T; Arora, V; Irving, P
Abstract: Background: Ulcerative colitis (UC) is a chronic disease characterised by inflammation of the rectum and colon. Bowel urgency, the sudden need for a bowel movement, is one of the most bothersome and important symptoms of UC. Treatment goals in UC focus on restoration of normal bowel frequency, control of primary symptoms of bleeding and urgency, and resolution of inflammation. The Urgency Numeric Rating Scale (NRS) is a newly developed patient-reported measure to assess the severity of the urgency to have a bowel movement in adult patients with UC. Methods: Development of the Urgency NRS was informed through semi-structured concept elicitation and cognitive debriefing interviews. The scale asks patients to report on the immediacy status of their UC symptom over the past 24 h on an 11-point horizontal NRS anchored at 0 (No urgency) and 10 (Worst possible urgency), with higher scores indicating worse urgency severity (i.e. immediacy of need to have a bowel movement). A 2-week daily diary pilot study was conducted to assess floor and ceiling effects, test–retest reliability and construct validity. Weekly average scores were calculated as mean score over each 7-day period. A bootstrapping simulation was used to assess test–retest with intraclass correlation coefficient (ICC) [≥0.70 = substantial agreement] between week 1 and week 2 scores. Content validity was assessed by Pearson and Spearman correlation with stool frequency (SF) and patient global rating of severity (PGR-S) scores using Cohen's conventions [ r ≥ 0.5 = large; 0.3 to ≤0.5 = moderate] using week 1 scores. Results: Through qualitative interviews, 16 adult UC patients (mean age 37.9 ± 11.6 years; 50% female; 56% White) confirmed relevance, item content and comprehensiveness of the Urgency NRS. Forty-one adult UC patients (mean age 44.2 ± 14.6 years; 51% female; 56% White) completed the 2-week study. Item distributions were uniform, with no ceiling or floor effects for the Urgency NRS (Figure 1). Test–retest reliability was high (ICC = 0.877), with simulated 95% confidence intervals ranging from 0.770 to 0.947. There was a high correlation between average urgency NRS and PGR-S scores, and a moderate correlation was observed between average Urgency NRS and number of stools in the first week (Table 1). Conclusion: Bowel urgency is an important symptom of UC, distinct from bowel frequency and rectal bleeding. The urgency NRS is a well-defined, content-valid and reliable measurement of bowel urgency that may be used to help characterise disease activity in adult patients with UC.